Peningkatan Kompetensi Bahasa Inggris Calon Alumni SMK Untuk Mendukung Program Direktorat SMK Melalui EPT Preparation - Ratini Setyowati; Beta Setiawati; Muhammad Iqbal (LPPM Universitas Duta Bangsa Surakarta, 2023)
English communication competence for SMK graduates is the target of all parties because SMK graduates are expected to be a workforce that is ready to work and compete. This program aims to improve English communication competence as a solution for the English communication competence of SMK graduates who have not been maximized. The method of implementing a community service program is divided into several stages, the first stage is the preparation, implementation, and evaluation of the program. The program was carried out at the Citra Medika Health Vocational School, Sukoharjo. The implementation of the program carried out using the Student Based Learning method, discussions, lectures, and practicing tests using the CBT English Proficiency Test from the Language Training Center of Duta Bangsa University. Training is given to prospective graduates for the 2021/2022 academic year, there were 145 participants. The program was carried out for about a month, each week had twice meetings. The result of this program was to find out the English communication competence of prospective graduate of Citra Medika Sukoharjo Health Vocational School. Based on the CBT English Proficiency Test result, the best score was 565, the lowest score was 100 and the average score was 228. Besides that there was more than 10% of students who had mastered good communication. Therefore, it is necessary to continue the program to improve the English communication skills of prospective Vocational High School graduates.